Statistical Methods with Applications in Data Mining: A Review of the Most Recent Works - Joaquim Fernando Pinto da Costa; Manuel Cabral (Mathematics, 2022)
The importance of statistical methods in finding patterns and trends in otherwise unstructured and complex large sets of data has grown over the past decade, as the amount of data produced keeps growing exponentially and knowledge obtained from understanding data allows to make quick and informed decisions that save time and provide a competitive advantage. For this reason, we have seen considerable advances over the past few years in statistical methods in data mining. This paper is a comprehensive and systematic review of these recent developments in the area of data mining.